1981
DOI: 10.1136/bmj.282.6279.1838
|View full text |Cite
|
Sign up to set email alerts
|

Reducing risks from intravenous cannulae.

Abstract: Addiction to benzodiazepines has been denied in some quarters on the basis that reported case histories do not fulfil the criteria of drug dependence.2 This case illustrates dramatically the four main features of dependence-namely, use of a drug to achieve its psychic effects, increase of dosage with time to achieve the same effects, experience of withdrawal symptoms on stopping the drug or reducing the dose, and abolition of withdrawal symptoms when the drug is reinstated. Short-acting benzodiazepine hypnotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…In a retrospective survey of disinfectants used for site care and tubing connections of Broviac catheters, Rannem et al (1990) reported 0.58 cases per catheter year with povidone iodine, vs <0.28% with 0.5% alcoholic iodine or chlorhexidine. In consecutive studies of peripheral cannulae, spraying the insertion site with 0.5% chlorhexidine gluconate in 70% industrial methylated spirit reduced the incidence of skin and tip colonisation and bacteraemia (Macfarlane et al 1981). These findings support the observation in this study of a lower rate of tip colonisation in catheters inserted with alcoholic chlorhexidine skin preparation as opposed to povidone iodine (Table 3.21 page 121).…”
supporting
confidence: 75%
“…In a retrospective survey of disinfectants used for site care and tubing connections of Broviac catheters, Rannem et al (1990) reported 0.58 cases per catheter year with povidone iodine, vs <0.28% with 0.5% alcoholic iodine or chlorhexidine. In consecutive studies of peripheral cannulae, spraying the insertion site with 0.5% chlorhexidine gluconate in 70% industrial methylated spirit reduced the incidence of skin and tip colonisation and bacteraemia (Macfarlane et al 1981). These findings support the observation in this study of a lower rate of tip colonisation in catheters inserted with alcoholic chlorhexidine skin preparation as opposed to povidone iodine (Table 3.21 page 121).…”
supporting
confidence: 75%
“…Several investigators have, however, reported factors of importance in preventing complications that arise when PIVs are used. Examples of those factors are good technique ( Hessov, 1985; Mossberg, 1993), good hygiene (Maki et al ., 1983), a well‐fixed small cannula ( Mossberg, 1993), good location ( MacFarlane et al ., 1980 ) and avoidance of hypo‐ or hypertonic solutions ( MacFarlane et al ., 1981 ; Hamory, 1987).…”
Section: Introductionmentioning
confidence: 84%
“…1 Careful hygiene is also an important aetiological factor. 2 The scale of symptoms given for thrombophlebitis varies but includes tenderness, redness, pain, swelling and increased temperature. 3 In severe cases a fibrosed band (from a thrombosed vein) occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombophlebitis has been shown to be related principally to the care and handling of intravenous cannulae 1 . Careful hygiene is also an important aetiological factor 2 . The scale of symptoms given for thrombophlebitis varies but includes tenderness, redness, pain, swelling and increased temperature 3 .…”
Section: Discussionmentioning
confidence: 99%